Sensitivity and Specificity of Rapid Diagnostic Tests (RDTs) in Detecting Plasmodium Vivax - C. Nagere, Andrew; D. Pijoh, Victor; S. B. Tuda, Josef (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: Malaria is an infectious disease caused by the Plasmodium genus of parasites. Plasmodium vivax is currently the most reported type of Plasmodium in Indonesia, accounting for 47.9% of cases. To reduce the incidence of malaria cases, a rapid, efficient, and affordable diagnostic method is needed, such as the Rapid Diagnostic Test (RDT). Objective: This study conducted laboratory tests on the RDT to evaluate its sensitivity and specificity in diagnosing malaria compared to the microscopic method, which is considered the gold standard. Method: This research employed an analytical study design using a cross-sectional approach. The data collected were processed and organized into contingency tables, calculating sensitivity, specificity, positive predictive value, and negative predictive value. Result and Discussion: The sensitivity of the RDT was found to be 92.59%, with a specificity of 100%. The positive predictive value was 100%, while the negative predictive value was 66.66%. Conclusion: This study concludes that the RDT diagnostic method is both sensitive and specific in detecting Plasmodium vivax when compared to the microscopic method as the gold standard.